2001
DOI: 10.1097/00005344-200104000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Platelet Activation in Stroke-Prone Spontaneously Hypertensive Rats: Comparison of Losartan, Candesartan, and Valsartan

Abstract: In vitro studies have suggested that losartan interacts with the thromboxane (TxA2)/ prostaglandin H2 (PGH2) receptor in human platelets, reducing TxA2-dependent platelet activation. The aim of this study was to evaluate the effect of different angiotensin II type 1 receptor antagonists in stroke-prone spontaneously hypertensive rats (SHRSP). The level of platelet activation was assessed by determining P-selectin expression in platelets by flow cytometry. The ex vivo adhesion of platelets was also analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This was not confirmed in the present study, because the reduction in BP by AT 1 R blockade with losartan administered was not altered by a concomitant treatment with C21 in the present study. However, it should be noted that the dose of losartan was not maximal, because a greater decrease in BP (45-100 mm Hg) has been observed with higher doses in SHRsp, 26,27 and the rats were still hypertensive at the end of the experiment. Thus, there was not complete prevention of genetic hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…This was not confirmed in the present study, because the reduction in BP by AT 1 R blockade with losartan administered was not altered by a concomitant treatment with C21 in the present study. However, it should be noted that the dose of losartan was not maximal, because a greater decrease in BP (45-100 mm Hg) has been observed with higher doses in SHRsp, 26,27 and the rats were still hypertensive at the end of the experiment. Thus, there was not complete prevention of genetic hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…[36][37][38][39][40] 28,30,33 and especially in elderly patients with isolated systolic hypertension. 29,31 Other mechanisms by which ARBs could reduce the incidence of new or recurrent stroke include the beneficial effects of some ARBs on blood glucose control by increasing insulin sensitivity, 49,50 their platelet antiaggregating effects, [51][52][53][54] their hypouricemic effects 66,67 and their atrial antifibrillatory effects. [69][70][71] All these actions of ARBs could add to their AII-mediated stroke protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of platelets from these animals with losartan decreased their adhesiveness to surfaces, whereas treatment with candesartan or valsartan had no significant effect on platelet adhesiveness. 52 These studies indicated that the action of losartan on platelet adhesion was not mediated through the AT 1 receptor because neither the losartan's metabolite EXP 3174, nor the other ARBs, candesartan and valsartan were able to prevent platelet adhesion or significantly suppress the expression of P-selectin on platelet surface. The increased expression of P-selectin on the platelet surface of SHR-SP has been blamed for the increased thrombogenicity and the higher incidence of strokes seen in these animals.…”
Section: Aii-mediated Effects Of Arbsmentioning
confidence: 99%
“…S2-S4). The most likely cause was that hypertension activated platelets and thrombus formation (28,29) and led to intravasal thrombi.…”
Section: Aii Induces Cardiac Hypertrophy In the Absence And Presence Ofmentioning
confidence: 99%